Control of the water compatibility and shape recovery of polyurethane using the graft polymerization of poly(ethylene glycol) methyl ether acrylate. (August 2020) - Chung, Yong-Chan; Kim, Ha Youn; Choi, Jae Won; Chun, Byoung Chul
Graft polymerization of poly(ethylene glycol) methyl ether acrylate (PEGA) onto polyurethane (PU) was conducted to improve its water compatibility, tensile mechanical strength, shape memory, and low-temperature flexibility properties, as well as to control its water vapor permeability (WVP). Control PUs containing free poly(PEGA) were also prepared to compare with the poly(PEGA)-grafted PUs. The water compatibility of PU notably improved due to the grafting of poly(PEGA) based on water contact angle results. The soft segment melting temperature and glass transition temperature were not changed with the increase in the PEGA content. The tensile strength of PU sharply increased due to the grafting of poly(PEGA), whereas the free poly(PEGA) in the control PUs did not cause a similar increase. The maximum strain of PU was not affected by the grafting of poly(PEGA). The shape recovery at 0°C significantly increased compared with the unmodified PU. The low-temperature flexibility of PU improved, and the WVP through the PU membrane was reduced by the grafting of poly(PEGA) onto PU.